Minimising claims being repudiated in the short-term insurance industry: concentrating on clients with Pleroma Brokers - Du Toit, M.J. (North-West University (South Africa), 2019)
In a highly competitive industry, service providers such as brokerages tend to lose clients because of claims being repudiated. When clients submit a claim, there is an expectation that they will be compensated for their loss. With the repudiation of a claim, the client suffers a financial or property loss, which leaves clients dissatisfied and leads to the cancellation of policies. The cancellation of policies has a negative effect on the bottom line of the service provider or, in this case, the brokerage. Therefore, there is a need to investigate why clients submit claims that are not covered in terms of the policy they entered into, as well as what can be done to minimize the submission of claims not covered in terms of a short-term insurance policy. The research study method used in this investigation will consist of an empirical study conducted through the utilization of a self-administered questionnaire completed by the respondents. Respondents are clients of Pleroma Brokers (Commercial) (Pty) Ltd, who currently have a short-term insurance product with the brokerage. The study established that it is important to make sure the service provider uses the most preferred communication channels to provide clients with important information. In addition, a high percentage of clients never read through their policy contract in its entirety, but in most cases, just focus on the initial section of their policy. A critical finding in the study is that clients confirmed that they struggle to understand the policy's wording and find the contract too long, confusing and overwhelming.
MBA, North-West University, Potchefstroom Campus, 2019
Keywords: Short-term insurance; repudiation; policy contract; client satisfaction; minimizing of claims; policy engagement